Semantic Expansion in Arabic Language Textbooks for the Preparatory Stage - Dakhil, Dr. Ali Abd (Thi Qar Arts Journal, 2024)
This research aims to identify “Semantic Expansion in Arabic Language Textbooks for the Preparatory Stage.” The researcher used a descriptive approach and content analysis method to achieve the research goal, as they are suitable for the purpose of the study. The research population and sample included exercises, drills, and activities from Arabic language textbooks for the preparatory stage. After reviewing sources related to his research topic, the researcher prepared patterns for semantic expansion, which included 15 patterns distributed across four main types. The first type included patterns related to “semantic expansion through semantic relationships between words,” consisting of 5 patterns. The second type included patterns of “morphological semantic expansion,” with 4 patterns. The third type included patterns of “grammatical semantic expansion,” also with 5 patterns. The fourth type included a pattern of “symbolic semantic expansion,” which is a primary pattern only. To verify their validity, they were presented to judges and specialists in the Arabic language, teaching methods, and in measurement and evaluation, and received an approval rate of 89% from the judges’ opinions. Then, the researcher analyzed the Arabic language textbooks for the preparatory stage in light of these patterns and extracted the stability of the analysis using the time-agreement method and G. Cooper’s equation, achieving a reliability coefficient of 100% in all books. The researcher relied on frequency as a unit of enumeration, using percentages and then a five-point scale to determine the weight of each pattern. The research results showed that all patterns of semantic expansion in Arabic language textbooks for the preparatory stage are not available (weak). The researcher concluded that the designers of the Arabic language curricula for the preparatory stage had neglected the semantic aspect and its expansion, which is the basis of communication among members of human societies and the foundation of advancement and prosperity; thus, it is the pulsating heart of linguistics. The ultimate goal of phonetic, morphological, and syntactic (grammatical) studies is to clarify meaning and remove ambiguity. This neglect is one of the main reasons for students’ weakness in reading comprehension and expressive performance. The researcher recommended the importance of including exercises, drills, and activities in Arabic language curricula that train students on how to expand semantically, so as not to limit their ability to express their ideas. It was suggested to build educational-training programs based on patterns of semantic expansion for teachers and students of the preparatory stage; as semantic expansion opens up horizons for students in choosing different words and linguistic structures to express their inner thoughts with ease and simplicity.